Examining the Relationship Between Diversity Exposure and Students' Color-Blind Racial Attitudes and Awareness of Racial Oppression. Issue 2 (3rd April 2019) - Priester, Mary Ann; Pitner, Ronald; Lackey, Richard
ABSTRACT: This cross-sectional study surveyed graduate-level social work and undergraduate psychology students ( N = 409) at a large university to explore the association of diversity exposure (diversity of undergraduate institution, diversity of childhood neighborhood, previous diversity courses), and color-blind racial attitudes and awareness of racial oppression. White students scored significantly higher on level of color-blind racial attitudes compared to racial/ethnic minorities. Students who attended predominantly White undergraduate institutions had greater awareness of racial oppression than students who attended racially balanced or institutions comprised exclusively of one racial/ethnic group other than White. Understanding how diversity exposure influences color-blind racial attitudes and awareness of racial oppression will better inform multicultural training and curricular delivery.